Risk Analysis Of Dropped Anchor Impact On Subsea Pipelines In Natuna - Adnyani, Luh Putri; Siregar, Hifzul Anwar; Putri, Destyariani Liana; Nurmawati, Nurmawati; Wirawan, Muhammad Khaisar (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2025)
Energy is a fundamental element in economic and social development, with oil and natural gas remaining the primary energy sources in Indonesia. To support the distribution of hydrocarbons from production facilities to onshore locations, subsea pipelines serve as vital infrastructure in the upstream oil and gas industry. However, subsea pipelines face various external risks, including dropped ship anchors, which can cause significant damage both technically and environmentally. This study aims to analyze the risk level of dropped anchors on subsea pipelines in Natuna. The methodology involves data collection related to pipeline characteristics, vessel traffic, and anchor types. Consequence analysis is conducted by calculating pipeline dent levels due to anchor kinetic energy based on the DNV-RP-F107 guideline. The results show that the anchor impact energy on the pipeline is approximately 3,94 kJ, placing the pipeline consequence level in the <5% dent/diameter category. Risk assessment using a risk matrix indicates that the risk level remains within the ALARP (As Low As Reasonably Practicable) threshold, meaning the risk is acceptable with reasonable mitigation measures. The findings suggest that although dropped anchors can cause pipeline deformation, the resulting damage remains within safe limits. However, to further reduce potential risks, additional mitigation measures are required, such as vessel traffic monitoring, designated anchor-free zones, and enhancing pipeline resilience against external impacts.